2013
DOI: 10.7314/apjcp.2013.14.10.5761
|View full text |Cite
|
Sign up to set email alerts
|

The XRCC1 Arg399Gln Genetic Polymorphism Contributes to Hepatocellular Carcinoma Susceptibility: An Updated Meta-analysis

Abstract: The potential correlation of X-ray repair cross-complementing group 1 (XRCC1) Arg399Gln polymorphism with hepatocellular carcinoma (HCC) susceptibility is ambiguous. Taking account of inconsistent results of previous meta-analyses and new emerging literatures, we conducted a meta-analysis covering 15 case-control datasets to evaluate the relationship. Relevant studies from Medline, Embase and CNKI were retrieved. A fixedeffect model or a random-effect model, depending on between-study heterogeneity, were appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 51 publications
(63 reference statements)
1
5
0
Order By: Relevance
“…These genotyping data are opposite to some studies 17 and in line with others. 12 , 14 , 16 The results, are identical to the findings of Li and colleagues who showed that XRCC1 Arg399Gln polymorphism was significantly associated with HCC susceptibility in Asian population. 23 But X.Y.Zeng shows that XRCC1 Arg399Gln was not significantly correlated to susceptibility to HCC.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…These genotyping data are opposite to some studies 17 and in line with others. 12 , 14 , 16 The results, are identical to the findings of Li and colleagues who showed that XRCC1 Arg399Gln polymorphism was significantly associated with HCC susceptibility in Asian population. 23 But X.Y.Zeng shows that XRCC1 Arg399Gln was not significantly correlated to susceptibility to HCC.…”
Section: Discussionsupporting
confidence: 86%
“… 22 Many research studies have evaluated the association between XRCC1 Arg399Gln gene polymorphism and HCC risk, but the results are controversial. 12 , 14 , 16 , 17 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have explored the impact of XRCC1 Arg399Gln polymorphism in various cancers including lung, gastric, esophageal, breast and prostate, as well as gliomas (7)(8)(9)(10)(11). However, association studies of XRCC1 Arg399Gln polymorphism in HCC risk have found conflicting results (12)(13)(14). XRCC1 genetic polymorphisms could be associated with increased risk of various neoplasms such as head and neck, bladder, breast or lung cancers (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Four published meta-analyses failed to observe any positive association between XRCC1 Arg399Gln polymorphism and HCC risk Liu et al, 2011;Xie et al, 2012;Zeng et al, 2013). Two articles (Chen et al, 2011;Pan et al, 2013) reported that XRCC1 Arg399Gln polymorphism was associated with the susceptibility to HCC in total population, but several papers published before 2011 were not included in Chen et al's study; In Pan et al's paper, one overlapping paper was not excluded and Long et al's paper (Long et al, 2006) with controls being not in accordance with Hardy-Weinberg equilibrium (HWE) was mistakenly included in Pan et al's paper. Li et al found that XRCC1 Arg399Gln polymorphism was associated with HCC risk in East Asian population , however, two overlapping studies were not excluded in that paper.…”
mentioning
confidence: 99%